Obtenção de sementes crioulas em sistemas de produção de base ecológica: uma experiência compartilhada a partir do melhoramento participativo da cultura do pimentão (Capsicum annuum var. annuum L.) - Silva, André Wagner Barata (2021)
One of the great challenges for organic farmers is the unavailability of vegetable cultivars adapted to their environmental conditions, management, and technological level. The cultivars must have good rusticity, resistance to pests and diseases, and production capacity under conditions of low solubility fertilizers to serve this segment. However, plant selection in conventional breeding programs has been typically conducted in more uniform environments, where the problems of biotic and abiotic stresses are minimized, making the selected materials little adapted to the environmental and handling conditions of organic farmers. One form to develop varieties adapted (creoles) to organic production systems is to place the breeding programs in the intended environment, directly on organic properties and in collaboration with the farmers. Therefore, the general objective of this research was to understand the possibility of building a shared experience in participatory genetic improvement of the bell-pepper culture with organic farmers from the Apan-Fé association. The specific objectives were to (i) identify genetic variability for different characteristics of interest in F2 bell-pepper plants originated from the cross between two open-pollinated cultivars (Ikeda and Itapetininga); (ii) understand the socio-environmental reality of farmers regarding the practice of organic agriculture and agroecology, and the meaning of Creole seeds for them, and promote the integration of scientific and popular knowledge linked to plant breeding. The research consisted of an association of research techniques in interface with extension. On the one hand, participatory breeding experiments for bell-pepper development were conducted on the properties of three farmers and in an experimental station. Qualitative data collection techniques were used simultaneously from January 2017 to July 2019, namely: participatory observation, field journal, semi-structured interviews, and focus group. During this period, the farmers also underwent training in the area of plant breeding. The analysis of fresh mass of bell-pepper fruits indicates the possibility of success in the selection made by the farmers through a participatory genetic improvement program using the genealogical method. This method aimed to obtain an open-pollinated cultivar with a higher average mass of fresh fruits, more adapted to environmental conditions (greater tolerance to low temperature) and the organic management of the agroecosystem. Likewise, the process of building knowledge in a shared form with farmers showed that they are potential agents for the conservation and sustainable use of agrobiodiversity, the maintenance of Creole varieties, and the balance of agroecosystems in Southern Minas Gerais. For farmers, Creole seeds mean autonomy, freedom, and spirituality. These are dimensions that come from the human being, from the world of meanings. In other words, the seed is not just a mere input. It represents the peasant resistance to the industrialization of agriculture, the appreciation of rural culture. This research innovates by enabling the interaction between the public institution (formal sector) and this community of farmers (informal sector) and promoting their community empowerment related to plant genetic improvement. The combination of quantitative and qualitative methods allowed the construction of a technology adapted to the agroecosystems and way of life from the socioenvironmental reality of this rural community.